Learning from Studs Terkel: listening while making places and spaces for effective interviews during fieldwork. Issue 2 (3rd May 2020) - Veeck, Gregory
ABSTRACT: Human geographers use many types of research techniques, often in a mixed methods format where multiple approaches and technologies are incorporated in a single study. This reflects the synthetic nature of our discipline, one of its central tenets and a major strength vis-à-vis other disciplines. Interviews are essential to many of our projects, and successful interviews are predicated on successful listening. However, interviewing is as much about being prepared and creating the places and spaces conducive for people to talk and for us to listen, as it is about listening and appreciating what others tell us. Inspired by the writings of the iconic Studs Terkel, this essay summarizes some of the major impediments to effective interviews and suggest some ways to overcome them. The effectiveness of interviews is as much determined by preparation and establishing the setting, timing, and pairings of the people present as it is on the questions asked, and the answers understood.